Le premier examen gynécologique de l'adolescente: Apprendre à l'adolescente à prendre charge de sa santé - Charbonneau, Louise (1991)
Increasingly, family physicians are expressing an interest in this facet of adolescent health care, realizing that a successful initial consultation offers tremendous educational opportunities. This article compares the use of a comprehensive questionnaire to a less formal approach. It describes various components of the pelvic examination that can teach adolescents to take responsibility for their health.